The Universal Constitutionalism in an Age of Religious Diversity. Western Secularism Tested by “New” Cultural Conflicts (Stato, Chiese e pluralismo confessionale, 2011)
An abridged version of this article (reported by Prof. Nicola Colaianni, University of Bari “Aldo Moro”) was presented at the Seminar on “Secularism and Liberal Constitutionalism”, held at the University of LUISS “Guido Carli” (Rome) on 6th July 2010.This article is due to be published in the International Review of Sociology, in 2011.SUMMARY: 1. Introduction – 2. Relation-Collaboration between the State and Churches in Constitutional Democracies – 3. The laicité à la française Tested by a Deprivatised Religious Process – 3.1. The French Rigid Secularism. Freedom (of Religion) through the State – 4. Canada’s Open Secularism. The  question of Religious-Based Family Law Disputes – 4.1 Reasonable Accommodation and “New” Religious Nomoi Groups – 5. Collaboration-Relation between the State and Churches in Italy – 5.1. The Italian Secularism Tested by the New “Religious Geography” – 6. Conclusion.Abstract Under the pressing process of immigration and globalisation many Western constitutional democracies have moved from a number of religions, sharing a common culture, to today's age of diversity. As opposed to the past, the current democracies are facing the lack of overlapping consensus over the basic constitutional laws: namely, the meaning and the scope of freedom of religion, secularism, the separation Church-State, equal treatment and the rule of law. This is because individuals often come to adopt their basic values by very different ways. The nature, scope and force of such values are likely to be affected by competing and, sometimes, contested fundamental values and worldviews. From here stems the pressing tension – or dilemma – between “unity” and “diversity”. This essay starts with general considerations about the freedom of religion principle, strictly related with the “separation” as well as “collaboration” between secular States and Churches; then the author analyses three case-studies (France, Canada and Italy), pointing out some specific legal approaches. In particular he focuses the analyses over the French “droit commun”, the Italian ecclesiastic law and the Canadian arbitral tribunals that, especially in family law, allow disputes to be arbitrated using religious jurisdictions.